Aromatherapy Using Lavender Oil Effectiveness on Pain and Anxiety After C-Section: A Randomized Controlled Trial - Mariem Nouira; Nesrine Souayeh; Sirine Aicha Kanzari; Hadhami Rouis; Amira Lika; Chaouki Mbarki; Fatma Zahra Rahali; Hajer Bettaieb (Journal of Epidemiology and Global Health)
Abstract Background Managing postoperative setting, regarding pain and anxiety after cesarean delivery is crucial for the mother’s recovery, her emotional well-being, mother-infant bonding and initiating breastfeeding. Although some research have suggested that aromatherapy with lavender essential oil can be effective in reducing pain and anxiety in various medical settings, the efficacy of lavender aromatherapy in the postoperative setting after cesarean delivery is less well-studied. We aimed to assess the effectiveness of lavender essential oil therapy in the management of pain and anxiety after cesarean delivery. Methods This was a monocentric randomized controlled double-blind trial conducted over a period of five months during 2023. A hundred women undergoing c-sections under spinal anesthesia were enrolled and randomly assigned; using block randomization of 4 items per block with allocation ratio 1:1, into two groups: The aromatherapy group (receiving inhaled Lavender essential oil) versus the placebo group (receiving distilled water instead). The primary outcomes were pain (at rest and after mobilization) and anxiety levels and after the intervention. This trial was registered on clinical-trials.org (NCT06387849). Results A total of 100 women were included (50 women in each group aromatherapy and the placebo group). The two groups were comparable regarding baseline characteristics and pre-intervention parameters with no statistically significant difference. After the intervention, the pain at rest (38,76 ± 22,9 vs. 23,84 ± 18,01; p < 0.001), the pain after mobilization (60,28 ± 23,72 vs. 40,12 ± 22,18; p < 0.001), and degree of anxiety (46,76 ± 6,59 vs. 44,3 ± 5,17; p = 0.03) were all significantly lower in the aromatherapy group. No adverse effects were reported by participants in both groups. Conclusion Aromatherapy using Lavender essential oil is effective in reducing pain and anxiety after cesarean delivery without adverse effects.